Safety Assessment of Composite Cylinders for Gas Storage by Statistical Methods : Potential for Design Optimisation Beyond Limits of Current Regulations and Standards /: Potential for Design Optimisation Beyond Limits of Current Regulations and Standards. (2017) - Mair, Georg W
No abstract available